D-STATCON model for voltage sag mitigation - Masdi, Hendri; Hasanah, Rini Nur; Suyono, Hadi; Musirin, Ismail Bin; Taufik, Taufik (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Development of a FACTS device model for mitigating voltage sag is presented. It deals with a static synchronous condenser (STATCON) to be used in the AC distribution networks. Simulation with the help of a commercial software Matlab/Simulink was explored to investigate its characteristics and performance during the voltage sag occurrence. The considered main cause of voltage sag was the starting of high capacity asynchronous motor. A voltage source inverter based on the phase-controlled thyristor components was implemented in this application to compensate the change in reactive power of the system. The concerns have been put on the influence of initial operation point and DC capacitance. The study results show the capability of D-STATCON model to reduce the consequence of voltage sag following the starting of high-power asynchronous motor in the distribution network. A fast response of the condenser work confirmed the desired performance.